Widely-tunable, multi-band Raman laser based on dispersion-managed thin-film lithium niobate microring resonators - Yanjing Zhao; Xiaoyue Liu; Kresten Yvind; Xinlun Cai; Minhao Pu (Communications Physics, 2023)
Abstract Stimulated Raman scattering is an attractive way to extend the operation spectral range of optical sources. However, the spectral extension range of a tunable Raman laser is limited by the Raman frequency shift and pump tuning bandwidth. This makes it challenging to realize chip-scale, widely tunable Raman lasers, as on-chip lasers only provide limited pump power and tuning bandwidth. Here, we tackle this by dispersion engineering of a thin-film lithium niobate microring resonator, where its high-quality factor ( ~ 2.5 million) ensures a sub-milli-watt (0.8 mW) threshold for Raman lasing while its strong normal dispersion with suppressed avoided mode crossing restrains the competing Kerr comb generation process. Combining the multi-wavelength Raman gain response of lithium niobate and cascaded Raman lasing, we demonstrate a widely tunable Raman laser covering 1592–1955 nm, showing a 335-nm spectral extension range from a 94-nm-tuning-bandwidth pump laser. Our demonstration paves the way to realize chip-scale, widely-tunable Raman lasers.